Teacher competency and work engagement among secondary school physical education teachers: the multiple mediating roles of occupational stress, emotional exhaustion, and professional achievement - Chen, Weisong; Huang, Zhen; Peng, Bo; Li, Lin; Chen, Jingsong (Frontiers in Psychiatry, 2025)
ObjectiveThis study examined the relationships between teacher competency, occupational stress, emotional exhaustion, sense of professional achievement, and work engagement among secondary school physical education teachers. It also investigated demographic differences in these variables and tested the structural invariance of the proposed model across genders.MethodA total of 1,347 secondary school physical education teachers participated in the study, completing validated scales to measure the key constructs and providing demographic information such as gender, age, education level, professional title, and school location. Data were analyzed using descriptive statistics, t-tests, one-way ANOVA, correlation analysis, and structural equation modeling (SEM). Mediation effects were assessed through bootstrapping, and structural invariance was tested using multigroup SEM.ResultsDemographic analyses revealed significant differences. Male teachers reported higher competency, professional achievement, and engagement, while female teachers experienced slightly greater emotional exhaustion. Younger teachers and those with lower professional titles reported higher occupational stress and emotional exhaustion. Rural and urban teachers exhibited comparable levels of most variables, except for urban teachers reporting slightly higher emotional exhaustion. Teacher competency directly influenced work engagement (28.27% of the total effect) and indirectly through occupational stress, emotional exhaustion, and professional achievement, with professional achievement being the strongest mediator (25.97% of the total effect). Sequential mediation pathways involving these factors were significant but weaker in magnitude. Structural invariance analysis confirmed that the model was consistent across genders, demonstrating robust applicability across male and female teacher populations.ConclusionTeacher competency is a key driver of work engagement, operating through both direct and indirect mechanisms, particularly by alleviating occupational stress and enhancing professional achievement. These findings underscore the importance of interventions aimed at fostering teacher well-being, including stress management programs and professional development opportunities, while addressing demographic-specific needs. Future research should employ longitudinal designs and consider additional contextual factors to extend these findings.